The adhesion of aluminium inserts in epoxy composites: The role of surface pre-treatment. (October 2022) - Sedonja, Štefan; Watts, John F.; Oldfield, Matthew; Sordon, Alessandro; Örn Gunnarsson, Gunnar; Viquerat, Andrew
Abstract: Aluminium inserts are frequently embedded within the composite sandwich structures used in modern sports cars. Since the inserts are used for attaching safety-critical components to the structure, the adhesion between the metal and composite needs to be strong and durable. The bond is achieved through an epoxy resin system. However, when the resin includes an internal mould release agent (IMR) to facilitate the demoulding process of the structure, the adhesion between the inserts and the composite structure can be compromised. In addition, inserts can be exposed to high treatment temperatures. As such, to ensure that high adhesion performance can still be achieved, an appropriate surface treatment should be applied on the inserts. In this paper, four commercially available surface treatments for aluminium inserts were assessed using single lap joint (SLJ) and double cantilever beam (DCB) tests. Moreover, to investigate the influence of the IMR and the high-temperature process on the joint properties, four sample manufacturing methods were used to prepare the SLJ samples: without IMR and without high-temperature process (Method 1), with IMR (Method 2), with high-temperature process (Method 3) and with both IMR and high-temperature process (Method 4). The DCB samples were only prepared using Method 4. The locus of failure for the SLJ samples prepared with Method 4 was evaluated by using X-ray photoelectron spectroscopy (XPS) and optical microscopy. It was found that a silane-based primer was sensitive to the use of both the IMR and high temperature (31% drop in the lap joint strength when both applied). A cataphoretic electrocoat was also investigated and only deteriorated when exposed to high temperature (up to 40% decrease in the lap joint strength). An epoxy-based primer did not show a significant sensitivity to the IMR, however, when exposed to high-temperatures, the joint became even stronger (up to 15% increase in the lap joint strength).